Is epidural analgesia still a viable option for enhanced recovery after abdominal surgery. Issue 5 (October 2018) - Weiss, Raphael; Pöpping, Daniel M.
Abstract : Purpose of review: Although thoracic epidural analgesia (TEA) is considered often as gold standard in multimodal analgesia with regard to major abdominal surgery, there is an ongoing debate if it is still a viable option for enhanced recovery because of its potential severe complications. Recent findings: In addition to the unsurpassed analgesic quality, a TEA offers several advantages. Studies have shown that a TEA does have a positive effect on perioperative morbidity and mortality, bowel function, the occurrence of ileus and patient mobility. Furthermore, TEA can reduce opioid-induced side effects, cardiac arrhythmias and pneumonia. When it is embedded into a multimodal fast-track program, it also shortens intensive care and hospital stay. Summary: TEA provides superior pain control with a handful of important advantages if used sensibly and with caution. Because of associated risks for severe neurological complications, clear contraindications should be ruled out. Special attention needs be paid to potential hypotension in the setting of epidural analgesia. If these key points are considered, a TEA still represents a viable option for enhanced recovery after major abdominal surgery.